2021
DOI: 10.36660/abc.20200233
|View full text |Cite
|
Sign up to set email alerts
|

Taxas de Mortalidade por Doenças Cardiovasculares e Câncer na População Brasileira com Idade entre 35 e 74 Anos, 1996-2017

Abstract: Fundamento: As doenças cardiovasculares (DCV) e câncer são as principais causas de morte no mundo. Essas doenças apresentam muitos fatores de risco em comum, e o controle de fatores de risco tradicionais para DCV foi associado com menor incidência de câncer. Objetivo: Analisar tendências nas taxas de mortalidade por câncer na população brasileira com idade entre 35 e 74 anos de 1996 a 2017. Métodos: As tendências nas taxas de mortalidade (bruta e ajustada por idade) foram analisadas quanto a todas as causas de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…The endogenous estrogen promotes vascular health through beneficial genomic and nongenomic mechanisms. A recent study on the Brazilian population aged 35 to 74 years between 1996 and 2017 showed that the age-adjusted death rate (DRaj) from CVD corresponded, on average, to 31% of deaths from all causes, but the death rate from CVD, IHD, and stroke was higher in men than in women [11]. Between 1996 and 2017, we observed a 38% reduction in CVD mortality in the Brazilian population.…”
Section: Introductionmentioning
confidence: 48%
“…The endogenous estrogen promotes vascular health through beneficial genomic and nongenomic mechanisms. A recent study on the Brazilian population aged 35 to 74 years between 1996 and 2017 showed that the age-adjusted death rate (DRaj) from CVD corresponded, on average, to 31% of deaths from all causes, but the death rate from CVD, IHD, and stroke was higher in men than in women [11]. Between 1996 and 2017, we observed a 38% reduction in CVD mortality in the Brazilian population.…”
Section: Introductionmentioning
confidence: 48%
“…De acordo com a Organização Pan-Americana de Saúde, as Doenças Cardiovasculares (DCV) são a principal causa de morte no mundo (OPAS, 2021). Com base nas taxas de mortalidade entre os anos de 1996 e 2017 disponíveis no Departamento de Informática do Sistema Único de Saúde (DATASUS), as DCVs corresponderam a 30% das mortes registradas no período (MANSUR; FAVARATO, 2021). Dentre os agravos das DCV, o Infarto Agudo do Miocárdio (IAM) acarreta perda de bem-estar, com redução dos anos de vida por incapacidade e morte prematura.…”
Section: Introductionunclassified